SOBRE O CONCEITO DE ALTERAÇÃO SUBSTANCIAL DE CADERNO DE ENCARGOS NO ÂMBITO DO PROCEDIMENTO PRÉ-CONTRATUAL PARA A REALIZAÇÃO DA EMPREITADA DE OBRAS PÚBLICAS (De Legibus - Law Journal, 2021)
This study addresses the concept of substantial modification in the framework of public procurement, reviewing national as well as European jurisprudence, and contributes to its clarification, being especially relevant as this concept constitutes the limit for the possible use of direct award for any contracts when previous public tender has failed either because no candidate has presented itself or no competitor has submitted a proposal, or all proposals have been excluded.